OUT COME OF PLATING, BONE GRAFTING AND SHORTENING OF NON-UNION HUMERAL DIAPHYSEAL FRACTURE - Khan, Mohammad Shoaib; Sahibzada, Ahmed Sohail; Khan, Mohammad Ayaz; Sultan, Shahid; Younas, Mohammed; Khan, Alam Zeb (Journal of Ayub Medical College Abbottabad, 2005)
Background: Humeral diaphyseal fracture usually heals with closed methods but when non union develops then it needs surgical intervention in the form of plating and bone grafting, intramedulary nailing (open or closed simple or interlocking nails) and external fixators (circular or one plane fixator). In our unit we treated non union humeral diaphyseal fracture with plating and bone grafting and shortening of fracture ends up to 4 to 5cm when needed. Methods: This study was conducted at Orthopaedic Department of Ayub Teaching Hospital Abbottabad from January 2002 till December 2003. We included 15 cases with atrophic non-union in 9(60%) and hypertrophic non-union in 6 (40%) patients. All atrophic non-union were treated with plating, bone shortening by transverse osteotomy and bone grafting, while hypertrophic non-union were treated with decortications of non-union ends and fixation with compression plates, with bone grafting in old age. Follow up measures were based on clinical (range of joints motion) and radiological (healing) findings. Follow up was done for upto 6 months. Results: Out of 15 patients the age range was 20-80 years, 12(80%) were male and 03(20%) female. Right humerus involved in 5(33.33%) while left humerus in 10(66.66%) patients. In 9(60%) patients with atrophic non union bone shortening by transverse cut osteotomy was done while in remaining patients with hypertrophic non-union plating was done in 2(13.33%) cases and plating with bone grafting in 4(26.66%) patients. Union was achieved in all patients after 16 to 20 weeks of surgery. In one patient (6.66%) of 75 years age with hypertrophic non-union implant was loosened after 03 months of surgery. At that time healing (Union) was evident on X-rays and humeral brace was applied for further 03 months. Two patients(13.33%) got neuropraxia of radial nerve which resolved with in 3 months time. 02 patients (13.33%) developed shoulder stiffness which resolved after exercise. Conclusion: In Non Union of Humerus shortening by transverse osteotomy & rigid fixation with plates give excellent results in selected cases. Key words: non-union, shortening, plating in bone grafting.